1994
DOI: 10.1002/hlca.19940770504
|View full text |Cite
|
Sign up to set email alerts
|

[M(bpy)3] (M = Fe, Ru, Os): New Crystalline Materials from the reductive electrocrystallization of [M(bpy)3](PF6)2

Abstract: Reductive electrocrystallization at a constant current density (1 1 .0-11.5 pA/cm2) of millimolar solutions of [ M (~~Y ) , ] ( P F~)~, where M = Fe, Ru, or Os, and bpy = 2,T-bipyridine in acetonitrile containing 0 . 1~ Bu4NPF, results in the formation of dark crystals on the Pt cathode. The crystals grow as long, thin, and shiny needles having a hexagonal cross section of 0.14.5 mm in diameter. 1.Introduction. -A recent article began by stating that 'tris(2,2'-bipyridine)ruthenium(II), Ru(bpy)?, has evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Unfortunately, we cannot define a spin ground state for [Fe(bpy) 3 ] 1from this result. It was therefore rather unexpected when in 1994 Echegoyen, Lehn et al [13] reported that crystalline solid samples of [M(bpy) 3 ] 0 (M = Fe, Ru, and Os) are EPR silent. In this case, a small Ru superhyperfine coupling of ca.…”
Section: Magnetic Susceptibility and Epr Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, we cannot define a spin ground state for [Fe(bpy) 3 ] 1from this result. It was therefore rather unexpected when in 1994 Echegoyen, Lehn et al [13] reported that crystalline solid samples of [M(bpy) 3 ] 0 (M = Fe, Ru, and Os) are EPR silent. In this case, a small Ru superhyperfine coupling of ca.…”
Section: Magnetic Susceptibility and Epr Spectroscopymentioning
confidence: 99%
“…[10,12] On the other hand, "clean" electrocrystallized samples of [Ru(bpy) 3 ] 0 and [Fe(bpy) 3 ] 0 have also been reported to be EPR silent. [13] The monoanions [M(bpy) 3 ] 1and [M(tpy) 2 ] 1-(M = Fe, Ru) have been electrochemically generated in CH 3 CN solution and are all EPR active (S = 1/2 signals). Additionally, solid Na[Fe(bpy) 3 ] has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…R bpy) 3 , where R = tBu (1) or Me (2), have been synthesized from reactions between AlX precursors (X = Cl, Br) and neutral R bpy ligands through an aluminum disproportion process. The crystalline compounds have been characterized by single-crystal X-ray diffraction, electrochemical experiments, EPR, magnetic susceptibility, and density functional theory (DFT) studies.…”
mentioning
confidence: 99%